159 Reactive Balance Training for Preventing Falls in Older People. (20th December 2019) - Sturnieks, Daina; Okubo, Yoshiro; Brodie, Matthew; Lord, Stephen
Abstract: Appropriately timed and directed balance responses are crucial for avoiding a fall. These responses, including feet-in-place adjustments of the centre of mass, stepping and gait adaptations, may be initiated voluntarily to proactively avoid falling or induced reactively in response to sudden external perturbations to balance. Despite good evidence that poor reactive balance responses contribute to falls and injuries, traditional fall prevention interventions have ignored this skill. Reactive balance (or perturbation) training intervention methods are emerging and show promise for preventing falls in older people, some evidence suggesting a 50% reduction in falls. We recruited 44 older adults into a parallel, blinded randomized controlled trial, comparing 3 sessions of reactive balance training (exposure to trips and slips) to one session of sham training. The primary outcome was falls following laboratory-induced trips and slips (>30% body weight in harness). Relative to the control group, the intervention group experienced fewer total falls (rate ratio [RR]=0.40, 95% confidence interval [CI]=0.22-0.76), slip falls (RR=0.33, 95% CI=0.12-0.90) and trip falls (RR=0.49, 95% CI=0.21-1.12). These results will be discussed in the context of other current evidence for reactive balance training and suggestions made for how such interventions might influence the future of fall prevention.